Systematic reviews as a "lens of evidence": Determinants of participation in breast cancer screening. (June 2021) - Mandrik, O; Tolma, E; Zielonke, N; Meheus, F; Ordóñez-Reyes, C; Severens, JL; Murillo, R
Objective: To assess the determinants of the participation rate in breast cancer screening programs by conducting a systematic review of reviews. Methods: We conducted a systematic search in PubMed via Medline, Scopus, Embase, and Cochrane identifying the literature up to April 2019. Out of 2258 revealed unique abstracts, we included 31 reviews, from which 25 were considered as systematic. We applied the Walsh & McPhee Systems Model of Clinical Preventive Care to systematize the determinants of screening participation. Results: The reviews, mainly in high-income settings, reported a wide range for breast cancer screening participation rate: 16–90%. The determinants of breast cancer screening participation were simple low-cost interventions such as invitation letters, basic information on screening, multiple reminders, fixed appointments, prompts from healthcare professionals, and healthcare organizational factors (e.g. close proximity to screening facility). More complex interventions (such as face-to-face counselling or home visits), mass media or improved access to transport should not be encouraged by policy makers unless other information appears. The repeated participation in mammography screening was consistently high, above 62%. Previous positive experience with screening influenced the repeated participation in screening programs. The reviews were inconsistent in the use of terminology related to breast cancer screening participation, which may have contributed to the heterogeneity in the reported outcomes. Conclusions: This study shows that consistent findings of systematic reviews bring more certainty into the conclusions on the effects of simple invitation techniques, fixed appointments and prompts, as well as healthcare organizational factors on promoting participation rate in screening mammography.